1989
DOI: 10.1002/mrm.1910110306
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional correlated spectroscopy (COSY) of intact frog muscle: Spectral pattern characterization and lactate quantitation

Abstract: Two-dimensional scalar-correlated 1H spectra (COSY) were recorded from a model solution containing varying amounts of lactate and a fixed concentration of carnosine as the reference compound. The integrated volume of the lactate methyl to methine cross peak in the magnitude-calculated spectra showed a linear increase with respect to lactate concentration. Accordingly, the COSY cross-peak integral volume should be a useful parameter for the quantitative study of metabolism in intact tissue. We have tested this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…A&s et al ( 11 ) have shown that the volume of the cross peaks in COSY spectra measured under homogeneous B1 field was proportional to the concentration of the product. To verify the reliability of this relationship in inhomogeneous B 1 field conditions we have constructed a calibration curve relating cross-peak volume ratios of glucose H,-H2 to total creatine verses a range of glucose concentrations ( 1, 5, 10, 15, and 20 mM) from phantom's solutions containing 50 m M KC1 and 10 m M total creatine.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…A&s et al ( 11 ) have shown that the volume of the cross peaks in COSY spectra measured under homogeneous B1 field was proportional to the concentration of the product. To verify the reliability of this relationship in inhomogeneous B 1 field conditions we have constructed a calibration curve relating cross-peak volume ratios of glucose H,-H2 to total creatine verses a range of glucose concentrations ( 1, 5, 10, 15, and 20 mM) from phantom's solutions containing 50 m M KC1 and 10 m M total creatine.…”
Section: Methodsmentioning
confidence: 98%
“…The time course of the quantitative changes in intracerebral glucose level was measured on the 2D spectra from the changes in the volume of the HI-H2 glucose cross peaks. The results (means k SEM) are expressed as the ratio of the volume of the correlation signal to the reference intensity of the Cr-PCr resonance, measured on the diagonal at 3.04 ppm (11). For each metabolite, all data were normalized to the basal level mean value taken as 100% (at time t = 0).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model solution, perchloric acid (PCA) extract, and tissue samples were prepared as described in ( 19). Grass frogs ( R a m pipiens leopard) were purchased from Charles D. Sullivan (Nashville, TN).…”
Section: Methodsmentioning
confidence: 99%
“…In this communication we compare the performance and information content of 2D homonuclear Hartmann-Hahn spectroscopy ( HOHAHA) with 2D doublequantum-filtered COSY (DQFCOSY) spectroscopy (19) in studies of metabolites in excised frog gastrocnemius muscle in the resting state. The results show the advantages of HOHAHA spectroscopy for the detection of metabolite patterns in intact tissue.…”
mentioning
confidence: 99%